Mediating Role Of Participation In Decision Making On The Relationship Between Core Self-Evaluation And Job Satisfaction - Salami, Ehsan (2010)
The purpose of this project paper is to examine the mediating role of seeking participation in decision making in the relationship between core self-evaluation (CSE) and job satisfaction. A correlational research design and survey method were used in this study. Respondents are comprised of 69 full time employees drawn from Malaysian small to medium private sectors companies from different industries.The results of the study have implications for management as well recruitment and selection process.